Long-Term Treatment With Ranirestat (AS-3201), a Potent Aldose Reductase Inhibitor, Suppresses Diabetic Neuropathy and Cataract Formation in Rats - Takafumi Matsumoto; Yoshiyuki Ono; Akemi Kuromiya; Kaoru Toyosawa; Yoshinaka Ueda; Vera Bril (Elsevier, 2008)
We investigated the chronic functional and histopathological changes in the sciatic nerve and lens of streptozotocin (STZ)-diabetic rats and evaluated the preventive effects of ranirestat (AS-3201), a potent aldose reductase inhibitor, on these changes. Sorbitol levels in the sciatic nerve and lens, motor nerve conduction velocity (MNCV), and development of cataracts were measured in STZ-diabetic rats given a ranirestat-admixed diet (0.0005%) for 35 weeks. Ranirestat reduced sorbitol accumulation in the sciatic nerve and improved the decrease in MNCV of STZ-diabetic rats. Morphological and morphometric examination of changes in sural nerve revealed that treatment with ranirestat prevented both the deformity of myelinated fibers and the decrease in their axonal and myelin areas (atrophy). Ranirestat also averted the changes in the size frequency histogram of myelinated fibers. Finally, STZ-diabetic rats developed early lens opacities 8 weeks after STZ injection and had cataract by the end of the experimental period. However, in the ranirestat-treated diabetic rats, no lens opacity was observed in any rat throughout the entire experimental period. This study suggests that the polyol pathway plays an important role in the progress of diabetic neuropathy and cataract formation in STZ-diabetic rats. Ranirestat should be a promising agent for the treatment of complications associated with diabetes, especially neuropathy. Keywords:: ranirestat (AS-3201), diabetic neuropathy, cataract, aldose reductase inhibition